Deep sequencing analysis of HIV‐1 reverse transcriptase at baseline and time of failure in patients receiving rilpivirine in the phase III studies ECHO and THRIVE. Issue 5 (5th October 2015) - Van Eygen, Veerle; Thys, Kim; Van Hove, Carl; Rimsky, Laurence T.; De Meyer, Sandra; Aerssens, Jeroen; Picchio, Gaston; Vingerhoets, Johan
Abstract : Minority variants (1.0–25.0%) were evaluated by deep sequencing (DS) at baseline and virological failure (VF) in a selection of antiretroviral treatment‐naïve, HIV‐1‐infected patients from the rilpivirine ECHO/THRIVE phase III studies. Linkage between frequently emerging resistance‐associated mutations (RAMs) was determined. DS (llIumina®) and population sequencing (PS) results were available at baseline for 47 VFs and time of failure for 48 VFs; and at baseline for 49 responders matched for baseline characteristics. Minority mutations were accurately detected at frequencies down to 1.2% of the HIV‐1 quasispecies. No baseline minority rilpivirine RAMs were detected in VFs; one responder carried 1.9% F227C. Baseline minority mutations associated with resistance to other non‐nucleoside reverse transcriptase inhibitors (NNRTIs) were detected in 8/47 VFs (17.0%) and 7/49 responders (14.3%). Baseline minority nucleoside/nucleotide reverse transcriptase inhibitor (NRTI) RAMs M184V and L210W were each detected in one VF (none in responders). At failure, two patients without NNRTI RAMs by PS carried minority rilpivirine RAMs K101E and/or E138K; and five additional patients carried other minority NNRTI RAMs V90I, V106I, V179I, V189I, and Y188H. Overall at failure, minority NNRTI RAMs and NRTI RAMs were found in 29/48 (60.4%) and 16/48 VFs (33.3%), respectively. Linkage analysis showed that E138K and K101E were usually not observed on the same viral genome. In conclusion, baseline minority rilpivirine RAMs and other NNRTI/NRTI RAMs were uncommon in the rilpivirine arm of the ECHO and THRIVE studies. DS at failure showed emerging NNRTI resistant minority variants in seven rilpivirine VFs who had no detectable NNRTI RAMs by PS. J. Med. Virol. 88:798–806, 2016 . © 2015 Wiley Periodicals, Inc.